Facile Preparation of TiO2 Nanobranch/Nanoparticle Hybrid Architecture with Enhanced Light Harvesting Properties for Dye-Sensitized Solar Cells. (26th October 2015) - Kim, Ju Seong; Shin, Seong Sik; Han, Hyun Soo; Shin, Sun; Suk, Jae Ho; Kang, Kisuk; Hong, Kug Sun; Cho, In Sun
Abstract : We report TiO2 nanobranches/nanoparticles (NBN) hybrid architectures that can be synthesized by a facile solution phase method. The hybrid architecture simultaneously improves light harvesting and charge collection performances for a dye-sensitized solar cell. First, TiO2 nanorods with a trunk length of 2 μ m were grown on a fluorine-doped tin oxide (FTO)/glass substrate, and then nanobranches and nanoparticles were deposited on the nanorods' trunks through a solution method using an aqueous TiCl3 solution at 80°C. The relative amount of nanobranches and nanoparticles can be controlled by multiplying the number of TiCl3 treatments to maximize the amount of surface area. We found that the resultant TiO2 NBN hybrid architecture greatly improves the amount of dye adsorption (five times compared to bare nanorods) due to the enhanced surface area, while maintaining a fast charge collection, leading to a three times higher current density and thus tripling the maximum power conversion efficiency for a dye-sensitized solar cell.